I sacramenti della Chiesa: Una rilettura teologico-giuridica - Visioli, Matteo (Quaderni di diritto ecclesiale, 2020)
The sacraments can be examined from a juridical perspective, but the condition that such a study is not undertaken in contrast or in parallel to a theological perspective. On the contrary, a canon lawyer can grasp the meaning of the sacraments of the Church only if he understands in his own reflection the nature of the sacraments as they emerge from the Word of God. The reasons that allow a juridical reading of the sacraments, which are instruments of grace, reside in the event of the incarnation of the Word, which assumes human nature with all that is entailed visibly and tangibly. Rights and duties therefore belong to the order of grace and as such find expression in canonical norms.